Risk factors for postpartum urinary incontinence - Leroy, Lígia da Silva; Lúcio, Adélia; Lopes, Maria Helena Baena de Moraes (Revista da Escola de Enfermagem da USP, 2016)
OBJECTIVE: To investigate the risk factors for postpartum urinary incontinence (UI) and its characteristics. METHOD: This was a case-control study with 344 puerperal women (77 cases and 267 controls) with up to 90 days postpartum. In a single session, participants were given a questionnaire with sociodemographic and clinical data and two others that assessed urine leakage, leakage situations, and type of UI. RESULTS: Stress UI was present in 45.5% of the women, incidents of urine leakage several times a day in 44.2%, of which 71.4% were in small amounts and 57.1% when coughing or sneezing. In 70.1% of cases, UI began during pregnancy and remained through the postpartum period. After running a binary logistic regression model, the following factors remained in the final model: UI during pregnancy (OR 12.82, CI 95% 6.94 - 23.81, p